Islamic Microfinance Institution Assistance Model in the Covid-19 Pandemic - Riduwan; Norma Sari; Sunu Prasetya Adi (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: Sharia Microfinance Institutions in the form of Baitul Mal wa Tamwil (BMT) is a form of financial inclusion that plays an important role in the development of micro and small businesses. Its main activity is to raise member funds in the form of deposits and redistribute them in the form of microfinance. During the covid 19 era, almost all of its members were affected, causing operational disruptions. Purpose: This study aims to analyze the impact of covid 19 on BMT and members as well as the social assistance model carried out until December 2021. Methodology: Determination of the sample using porpusive sampling with respondents as many as 43 BMT spread across Sumatra, Java and Sulawesi. The three islands were chosen because they became the center of BMT's growth.  The data collection method uses google form, while the data analysis uses qualitative descriptive analysis. Findings: The results of the analysis show that covid 19 has a direct impact on BMT's performance by an average of 8.4%, in the form of a decrease in financing installments, deposits and profits as well as an increase in non-performing financing. Although BMT's performance has decreased, its social role has increased in the form of social assistance, such as relaxation of financing, member education and facilitation of marketing of member products through social media, and the provision of basic social assistance.